Preliminary Feasibility Studies of Vegetable Oil as Substitution to Mineral Lubricant / Muhammad Aizat MD Alias and Muhamad Azwar Azhari - MD Alias, Muhammad Aizat; Azhari, Muhamad Azwar (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The negative factor of mineral oil such as non-biodegradable and toxic influence many researcher to discover the new alternatives lubricant in order to substitute the mineral oils. However, there is restriction when using vegetable oil as lubricant which is there have low oxidation stability which can leads to low lubricity performance. This paper studies the physical and chemical properties in terms of coefficient of friction, wear scar diameter and flash point of vegetable oils and mineral oils. It is expected that the vegetable oils have a higher value of a flash point than mineral oils and lower lubricity performance than mineral oils due to the presence of additive in mineral oils.